Dari Lokasi ke Layanan: Dampak Lokasi dan Kualitas Layanan pada Loyalitas Tamu di Mediasi oleh Pengalaman Tamu - Danny Philipe Bukidz; Joselyn Chandrigo (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study analyzes the impact of location and service quality on guest loyalty at Aryaduta Hotel Medan, with guest experience as a mediating variable. Using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method, this research involved 100 respondents who had stayed at the hotel. The results show that location does not have a direct significant effect on guest loyalty (coefficient 0.087; p=0.1410), but it significantly enhances guest experience (coefficient 0.386; p=0.0000). Conversely, service quality has a direct significant effect on guest loyalty (coefficient 0.412; p=0.0010) and also improves guest experience (coefficient 0.401; p=0.0000). Guest experience is a significant mediator in the relationship between location and guest loyalty (coefficient 0.182; p=0.0010) as well as between service quality and guest loyalty (coefficient 0.189; p=0.0000). These findings confirmed the importance of guest experience in building customer loyalty. Strategic recommendations include enhancing service quality, optimizing location, and developing more personalized guest experience programs. This study provides insights for the hospitality industry more effective and sustainable customer retention.